REGIONAL FEATURES OF ENTREPRENEURSHIP DEVELOPMENT - Fayziyeva, Shirin (THE INNOVATION ECONOMY, 2024)
This scientific article analyzes regional characteristics, significance and created opportunities for stimulating entrepreneurship in our country. Data on points of growth of entrepreneurial activity and the share of small businesses in the main sectors of the economy of the Kashkadarya region and districts were compared. The system of state support for business and entrepreneurship in Uzbekistan is being implemented in order to improve the well-being of the population, strengthen the country’s economy, and also reflects the assigned tasks based on measures aimed at developing small businesses and private entrepreneurship. in the article. The importance of adopting legislation on social entrepreneurship, a favorable business environment in our country, created privileges and opportunities for foreign investors that serve the implementation of new projects was also shown. This plays an important role in eliminating existing obstacles and pitfalls as a result of reforms for the development of industry activities carried out by our state, as well as in ensuring stability and further development of enterprises. Determining the main directions for the development of entrepreneurship, the study of issues of integrated development of entrepreneurship and the creation of opportunities in the main department of economic development and poverty reduction of the Kashkadarya region indicates the relevance of the topic of this article. The inclusion of issues of supporting individuals engaged in entrepreneurial activities, that is, manufacturers and service providers, creating conditions, strengthening the supply of new technologies, and further developing mechanisms for state support for exports increases its importance.